Sodium Tanshinone IIA Sulfonate Inhibits Vascular Endothelial Cell Pyroptosis via the AMPK Signaling Pathway in Atherosclerosis - Zhu J; Chen H; Guo J; Zha C; Lu D (Dove Medical Press, 2022)
Ji Zhu,1,* Hang Chen,2,* Jianan Guo,2 Chen Zha,1 Dezhao Lu2 1The Third Affiliated Hospital of Zhejiang Chinese Medical University (Zhongshan Hospital of Zhejiang Province), Hangzhou, People's Republic of China; 2School of Life Sciences, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Dezhao Lu, Email ludezhao@126.comIntroduction: Atherosclerosis (AS) is the underlying cause of cardiovascular events. Endothelial cell mitochondrial damage and pyroptosis are important factors contributing to AS. Changes in internal mitochondrial conformation and increase in reactive oxygen species (ROS) lead to the disruption of mitochondrial energy metabolism, activation of the NLRP3 inflammasome and pyroptosis, which in turn affect atherogenesis by impairing endothelial function. AMPK is a core player in the regulation of cellular metabolism, not only by regulating mitochondrial homeostasis but also by regulating cellular inflammatory responses. Sodium tanshinone IIA sulfonate (STS), a water-soluble derivative of tanshinone IIA, has significant antioxidant and anti-inflammatory effects, and roles in cardiovascular protection.Purpose: In this study, we investigated whether STS plays a protective role in AS by regulating endothelial cell mitochondrial function and pyroptosis through an AMPK-dependent mitochondrial pathway.Methods and Results: Male ApoE−/− mice and HUVECs were used for the experiments. We found that STS treatment largely abrogated the upregulation of key proteins in aortic vessel wall plaques and typical pyroptosis signaling in ApoE−/− mice fed a western diet, consequently enhancing pAMPK expression, plaque stabilization, and anti-inflammatory responses. Consistently, STS pretreatment inhibited cholesterol crystallization (CC) -induced cell pyroptosis and activated pAMPK expression. In vitro, using HUVECs, we further found that STS treatment ameliorated mitochondrial ROS caused by CC, as evidenced by the finding that STS inhibited mitochondrial damage caused by CC. The improvement of endothelial cell mitochondrial function by STS is blocked by dorsomorphin (AMPK inhibitor). Consistently, the blockade of endothelial cell pyroptosis by STS is disrupted by dorsomorphin.Conclusion: Our results suggest that STS enhances maintenance of mitochondrial homeostasis and inhibits mitochondrial ROS overproduction via AMPK, thereby improving endothelial cell pyroptosis during AS.Keywords: atherosclerosis, pyroptosis, tanshinone IIA, AMPK, mitochondria